GRATE BAR WITH PROTECTION ELEMENT OF CERAMIC MATERIAL OR EQUIVALENT MATERIAL OF HIGH HEAT AND WEAR RESISTANCE - CRIPPA, LIVIO (1991)
The grate bar used particularly in the grates of incineration furnaces, which are normally formed with a bed consisting of rows of grate bars supported by two frames driven with reciprocating motion to feed the fuel along the grates. The grate bars are subject to considerable erosion due to their rubbing against each other and against the overlying material to be burned, and are also obviously exposed to the flames so that they are subject to rapid oxidation and wear. To reduce said wear and oxidation phenomena, the grate bar according to the invention consists of a lower element (5) with a load-bearing function, constructed of steel or cast iron without particular heat or abrasion resistance characteristics, and an upper element (6) formed of ceramic material or another equivalent material.